Analisis Kecemasan Ibu Bersalin Saat Pandemi Covid-19 Terhadap Keberhasilan IMD di Wilayah Kerja Puskesmas Somba Opu Gowa Tahun 2022 - Rika Rika (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Pregnant women are a group that is vulnerable to infection with the COVID-19 virus. This is because pregnant women experience physiological changes in the body including changes in the immune system. During the pregnancy period there is a decrease in lymphocytes, a decrease in natural killer cells, and an increase in pro-inflammatory factors which make pregnant women susceptible to infection with viruses, including COVID-19. The impact of COVID-19 infection on the fetus is that 30% experience fetal distress and 37% premature birth. Anxiety is a feeling that exists in every human being. Anxious because of factors that could endanger himself or his family, thus causing discomfort in life. The anxiety of pregnant women is increasing especially during the Covid-19 pandemic. Most pregnant women are worried about the impact of the corona virus on the birth of their babies, where pregnant women are afraid of being infected with Covid-19. Due to excessive anxiety finally the mother chooses to give birth alone. This anxiety affects the success of Early Breastfeeding Initiation (IMD). Pregnant women experience increased anxiety during the COVID-19 pandemic. Methods: This study uses an analytic survey method using a cross-sectional approach which is used to examine an event at the same time. In this study, the samples taken were all mothers in the working area of ​​the Somba Opu Gowa Health Center who were met by researchers during the research process. Results: From the results of the statistical test the P-Value was 0.000 <0.05 so that there was a significant relationship between the anxiety of mothers giving birth during the Covid 19 Pandemic to the success of IMD. Conclusion: There is a significant relationship between maternal anxiety during the Covid 19 Pandemic and the success of IMD